2020
DOI: 10.3389/fnins.2020.00650
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Brain Renin-Angiotensin-System (RAS) and Inflammation in the Sensitization of Hypertension

Abstract: Mounting evidence indicates that the renin-angiotensin (RAS) and immune systems interact with one another in the central nervous system (CNS) and that they are importantly involved in the pathogenesis of hypertension. Components comprising the classic RAS were first identified in the periphery, and subsequently, similar factors were found to be generated de novo in many different organs including the brain. There is humoral-neural coupling between the systemic and brain RASs, which is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 123 publications
3
28
0
Order By: Relevance
“…In obese humans and in animal models of diet‐induced obesity, increased sympathetic nervous system activity and BP have been demonstrated to be associated with RAS activation, elevation of inflammation, and increased leptin peripherally and centrally. 13 , 16 , 19 , 32 , 33 Consistent with this, we found that HFD‐fed offspring exhibited increased BP, elevated levels of angiotensin II, interleukin‐6, and leptin in the plasma and increased centrally driven sympathetic activity. The increased BP and central sympathetic tone were greater in HFD‐fed offspring of hypertensive dams when compared with HFD‐fed offspring of normotensive dams.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In obese humans and in animal models of diet‐induced obesity, increased sympathetic nervous system activity and BP have been demonstrated to be associated with RAS activation, elevation of inflammation, and increased leptin peripherally and centrally. 13 , 16 , 19 , 32 , 33 Consistent with this, we found that HFD‐fed offspring exhibited increased BP, elevated levels of angiotensin II, interleukin‐6, and leptin in the plasma and increased centrally driven sympathetic activity. The increased BP and central sympathetic tone were greater in HFD‐fed offspring of hypertensive dams when compared with HFD‐fed offspring of normotensive dams.…”
Section: Discussionsupporting
confidence: 84%
“… 38 , 39 In the central neural network, RAS components, inflammatory factors and leptin act on these structures to alter neural processing and storage information to establish a new level of sympathetic nervous system basal activity and reactivity to stressors, such as seen with obesity‐related hypertension. 16 , 19 , 32 , 40 To explore the central mechanisms underlying maternal hypertension sensitization of postweaning HFD‐induced increase in BP, we determined the pressor effects of intracerebroventricular application of angiotensin II, TNF‐α, or leptin in offspring. We found that although LFD‐fed offspring of hypertensive dam had a normal baseline BP, they exhibited increased pressor responses to intracerebroventricular angiotensin II and to TNF‐α.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously noted, the regulation of Ang II and TLR4 involves the body–brain communication between afferent neural and humoral pathways that activate the central neural network to control cardiovascular function [ 36 ]. Neither RAS nor inflammatory mediators can contribute individually to the pathogenesis of hypertension; thus, the interactions between RAS components and inflammation mediators are likely synergistic [ 37 ]. Our findings concluded that the downregulation of AT1R-induced superoxide generation is associated with the activation of microglia and the expression of TLR4 in the NTS of SHR.…”
Section: Discussionmentioning
confidence: 99%